A poesia no ensino de Libras como língua adicional - Araújo, Klébia Souza (2024)
This research focuses on the proposal to link deaf poetry in the context of teaching Brazilian Sign Language (Libras) to hearing students, as an additional language, in a perspective that goes beyond learning the language itself, encompassing different cultural and linguistic perceptions. and identity. The general objective of this study is to verify the feasibility of using poetry in sign language (poetry in LS) as a teaching resource in teaching Libras as an additional language. The research has theoretical support from authors such as: Vygotsky (1991), Moisés (1997), Pound (2006), Figliolo (2016), Figueiredo (2019), Souza, Ribeiro and Faria (2020), Silva and Lago (2020) , Bernardino, Pereira and Passos (2020), Regino (2021) and Sutton-Spence (2021). The research is participatory and has a qualitative approach, as it presupposes collaboration between the researcher and the participants in the search to understand what, in fact, happens from the perspective of these members, valuing their knowledge and experiences. Data collection takes place in a class made up of students from different degrees, but predominantly from the Literature: Portuguese course, from the Faculty of Arts of the Federal University of Goiás (UFG). In this study, Libras teaching classes are proposed through poetry in sign language (SL), the majority of which are written by deaf poets and, during this process, filming and recordings are used as data collection instruments in the Records Diary. According to an evaluation carried out with the students who participated in the research, the results indicate the viability of poetry in LS as a teaching resource in teaching Libras to listeners, since poetry in LS sharpens students' interest and positively influences their connection with the language. Libras, fostering curiosity and respect not only for sign language, but also for the deaf community, its history and culture.